Pengaruh Paid-Owned-Earned Media, Voucher Diskon, dan Kesadaran Halal terhadap Keputusan Pembelian Generasi Z Muslim pada Platform Online Food Delivery di Bandung Raya: The Influence of Paid-Owned-Earned Media, Discount Vouchers, and Halal Awareness on Purchase Decisions of Muslim Generation Z on Online Food Delivery Platforms in Bandung Raya - Nazwa Izzati Nisa (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
The rapid growth of the digital economy in Indonesia has positioned Online Food Delivery (OFD) platforms as a primary consumption instrument for Muslim Generation Z; however, a paradox exists between a pragmatic digital lifestyle and the principles of halal awareness. This study aims to analyze the influence of Paid-Owned-Earned Media (POEM), discount vouchers, and halal awareness on the purchase decisions of Muslim Generation Z in the Greater Bandung area. Utilizing a quantitative method with the PLS-SEM approach on 200 respondents, the results indicate that POEM and discount vouchers have a positive and significant effect on purchase decisions ( > 1.96; < 0.05). Conversely, halal awareness was found to have no significant effect ( = 1.453; = 0.146), suggesting a phenomenon of internalized trust where consumers assume that the platform's verification system already guarantees product halalness. The originality of this research lies in the integration of the POEM framework with Islamic economic perspectives, such as the implementation of the DSN-MUI Fatwa regarding discounts within the digital ecosystem. These findings are beneficial for OFD service providers to align promotional strategies with strengthened halal certification transparency to build sustainable loyalty among Muslim consumers. Furthermore, this study serves as an academic reference in enriching the literature on Muslim consumer behavior in the digital native era.